Analysis and Improvement of Rubber Roll Production Line Balancing Using Ranked Positional Weight (RPW) and Region Approach Methods at CV. ABC - Fatur Rahman; Wiwin Widiasih (Jurnal Ilmiah Teknik, 2026)
The rubber roll production line at CV. ABC exhibited considerable workload imbalance among workstations, particularly at the steam and turning processes. Differences in processing times resulted in potential bottlenecks, high balance delay, and inefficient utilization of available production-line capacity. Objective: This study aims to analyze the existing rubber roll production-line balance and compare the Ranked Positional Weight (RPW) and Region Approach methods to identify a workstation configuration with improved line utilization and more uniform workload distribution. Methodology: A quantitative engineering case-study approach was applied. Primary data were collected through direct observation, interviews, documentation, and stopwatch time study, while secondary data were obtained from company production records and relevant literature. Processing-time data, precedence relationships, performance ratings, and allowances were analyzed to determine work-element times and production-line characteristics. The existing configuration was evaluated using line efficiency, balance delay, idle time, and smoothness index. Work elements were subsequently reallocated using RPW and the Region Approach, and the resulting production-line performances were compared. Findings: The existing production line consisted of six workstations with a line efficiency of 52%, a balance delay of 48%, and a smoothness index of 214.04. Both RPW and the Region Approach reduced the number of workstations to five and increased line efficiency to 70%, while balance delay decreased to 30%. However, RPW produced a smoothness index of 117.4179, considerably lower than the 223.29228 obtained using the Region Approach. The RPW configuration also resulted in a total idle time of 204.38 min, indicating improved utilization of available workstation capacity. Implications: The findings provide an engineering basis for reorganizing work-element allocation in rubber roll production. The proposed RPW configuration can support more uniform workstation loading and improve production-flow efficiency, particularly in manufacturing processes with substantial variation in processing times. Originality: This study provides a direct comparison between cumulative positional-weight allocation and precedence-region grouping under the same rubber roll production conditions. The results demonstrate that identical line efficiency and balance delay do not necessarily indicate equivalent workload uniformity, highlighting the importance of smoothness index as a complementary criterion for selecting a line-balancing configuration.